Enhanced cellulosic d-lactic acid production from sugarcane bagasse by pre-fermentation of water-soluble carbohydrates before acid pretreatment. (January 2023) - Qiu, Zhongyang; Han, Xushen; Fu, Anqing; Jiang, Yalan; Zhang, Wenyue; Jin, Ci; Li, Dengchao; Xia, Jun; He, Jianlong; Deng, Yuanfang; Xu, Ning; Liu, Xiaoyan; et al.
Graphical abstract: Highlights: 98% of WSC in sugarcane bagasse was converted to d -lactic acid before pretreatment. The obtained d -lactic acid stably preserved in sugarcane bagasse after pretreatment. HMF production was sharply reduced after pretreatment due to WSC pre-fermentation. WSC pre-fermentation also improved d -lactic acid production by one-pot SSCF. Abstract: After several rounds of milling process for sugars extraction from sugarcane, certain amounts of water-soluble carbohydrates (WSC) still remain in sugarcane bagasse. It is a bottleneck to utilize WSC in sugarcane bagasse biorefinery, since these sugars are easily degraded into inhibitors during pretreatment. Herein, a simple pre-fermentation step before pretreatment was conducted, and 98 % of WSC in bagasse was fermented into d -lactic acid. The obtained d -lactic acid was stably preserved in bagasse and 5-hydroxymethylfurfural (HMF) generation was sharply reduced from 46.0 mg/g to 6.2 mg/g of dry bagasse, after dilute acid pretreatment. Consequently, a higher d -lactic acid titer (57.0 g/L vs 33.2 g/L) was achieved from the whole slurry of the undetoxified and pretreated sugarcane bagasse by one-pot simultaneous saccharification and co-fermentation (SSCF), with the overall yield of 0.58 g/g dry bagasse. This study gave an efficient strategy for enhancing lactic acid production using the lignocellulosic waste from sugar industry.